1977
DOI: 10.2134/agronj1977.00021962006900010011x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Corn and Sorghum Grain in Double‐Cropping Systems1

Abstract: Double‐cropping systems involving no‐till planting are becoming popular in the southeastern USA, but adequate management practices have not been developed. Therefore, this study was conducted to determine the effects of the following tillage systems. Corn [Zea mays (L.)] and grain sorghum [Sorghum bicolor (L.)] were planted without tillage following winter wheat [Triticum aestirum (L.)] or barley [Hordeum vulgate (L.)] and with conventional tillage following previous summer crop at two locations in Georgia for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…To minimize the effect of soil-water depletion by cover crops, early herbicide desiccation, animal grazing, or mechanical harvesting could be used (Campbell et al, 1984). The effectiveness of a cover crop in maintaining or improving soil water storage also depends on other factors such as: cover crop species, method of planting, stage of growth, length and growth period, method of extermination, leaving the crop as a mulch or green manure (Moschler et al, 1967;Nelson et al, 1977;Campbell et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the effect of soil-water depletion by cover crops, early herbicide desiccation, animal grazing, or mechanical harvesting could be used (Campbell et al, 1984). The effectiveness of a cover crop in maintaining or improving soil water storage also depends on other factors such as: cover crop species, method of planting, stage of growth, length and growth period, method of extermination, leaving the crop as a mulch or green manure (Moschler et al, 1967;Nelson et al, 1977;Campbell et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The use of minimum-tilled or reduced-tilled practices in other crops such as com, grain sorghum, or soybeans has reduced production cost, soil erosion and water runoff (5,8,9,10,11,16). Unger and co-workers (17) noted that the presence of crop residue on the soil surface could nearly eliminate erosion problems.…”
mentioning
confidence: 99%
“…A Significant genotype x tillage system interaction was apparent for SMK + SS. TX835820 and TX835841 grades were Significantly lower with no-tillage systems while other cultivars produced no significant changes in grade.Key Words: Groundnut, Sclerotium rolfsii, southern blight, notillage, minimum-tillage.The use of minimum-tillage and no-tillage production practices has reduced production costs in com, grain sorghum, soybeans, and other crops (1,10,13,14,15,16,18,19,21). However, limited research (2,3,4,5,6,7,8,9,11) has been reported with the use ofno-tillage cultural practices in peanuts.…”
mentioning
confidence: 99%